Prevalence and Assessment of Risk Factors of COVID-19: A Retrospective Study from Southern India - M. Revathi; B. Usharani; R. Venkateswari; P. Gunavathy; M. Anbazhagi; M. Muthuraj (Disease and Health Research: New Insights Vol. 4, 2024)
Background: A research study was carried out to determine the prevalence and incidence of COVID-19 and to identify the risk factors associated with infection. The Xpert Xpress SARS-CoV-2 assay was utilized to detect COVID-19. Methods: Out of 1001 patients tested, 119 (11.9%) tested positive for COVID-19, with 5.3% females and 6.6% males. The highest percentage of positive cases was found among symptomatic patients with influenza-like illness (ILI symptoms) in a healthcare setting and among individuals who chose to get tested. Results: Our multivariable logistic regression analysis revealed the risk factors associated with COVID-19 transmission. The relative risk (RR) indicates the ratio of risk (probability), where RR > 1 shows that exposure increases risk, and RR < 1 indicates that exposure is protective against risk. The analysis showed that being female (RR=1.10; 95%CI: 0.79-1.55), aged between 46-60 (RR=1.19; 95%CI: 0.75-1.87), all asymptomatic high-risk individuals (RR=2.79; 95%CI: 0.35-22.20), and all symptomatic patients with ILI symptoms in a healthcare setting (RR=3.64; 95%CI: 2.05-6.44) are associated with a higher prevalence of COVID-19. Conclusion: Despite consistent exposure at work, we observed a modest incidence of COVID-19. Community contact was strongly associated with infections, but contact at work was not unless accompanied by high-risk exposure.